Budgetary Management Efficiency and Profitability in Manufacturing Firms the Moderating Role of Firm Size - Velia Putri Safira; Bintoro Bagus Purnomo; Anggraini Syahputri; Giriati; Wendy (Al-Qalam Institue, 2026)
This study aims to analyze the effect of budget management efficiency on corporate financial performance by considering firm size as a moderating variable. Budget management efficiency is measured through three dimensions: operational efficiency, working capital efficiency, and investment decisions, while financial performance is measured using Return on Assets (ROA). This study employs a quantitative approach using panel data regression and Moderated Regression Analysis (MRA). The sample was selected using purposive sampling, resulting in 200 firm-year observations from 40 companies that met the research criteria during the observation period. The results indicate that operational efficiency and investment decisions do not have a significant effect on profitability, whereas working capital efficiency has a positive and significant effect on profitability. Furthermore, firm size does not significantly moderate the relationship between operational efficiency, working capital efficiency, investment decisions, and profitability. These findings imply that effective working capital management is a critical factor in improving financial performance because the optimization of current assets, including cash, receivables, and inventory, directly supports profitability improvement. This study contributes to financial management literature by highlighting the importance of internal resource efficiency rather than company scale in achieving sustainable financial performance.